(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the present time, technology has turned into an Integral piece of our lives. Consistently there is new gadget or software that makes lives simpler. Making lives simpler isn’t, be that as it may, the main job the technology plays in our lives. Truth be told, it is assuming key job in improving each part of life. Technology has opened new ways to immaculate parts of life and has colossally influenced each field of human life. The field of education isn’t a special case. It is assuming an expanding job in the field of education. Technology has additionally progressed to enable children to even before they have begun school. Educational computer games and software for youthful children help them get ready for school and at times get a head begin their education. Information and communication technologies are helping in changing the educational condition. Technology in educational field is changing the customary job of the partners of education. New information and communication technology has presented numerous adjustments in the present educational system. Intelligent technologies have influenced the very idea of teaching and learning. In this Research Study. We studied a Conceptual Study on ICT Access in Education Sector and its Advantages.